Finding me a decade of darkness, a life reclaimed : a memoir of the Cleveland kidnappings - Knight, Michelle 1981-; Burford, Michelle (Weinstein Books, 2014)
Describes the details of the abduction and decade-long captivity of one of the three survivors of notorious Cleveland kidnapper Ariel Castro, and how she found the courage to endure unimaginable circumstances and never lose hope for the future.